(untitled) (Географический вестник=Geographical bulletin, 2017)
Показано влияние отраслей хозяйства на формирование и поддержание очагов клещевого энцефалита и геморрагической лихорадки с почечным синдромом. Оценена эпидемиологическая ситуация по природно-очаговым заболеваниям в Пермском крае, для чего предложен прием ранжирования территории по интегральному показателю. К л ю ч е в ы е с л о в а: эндемический зооноз; клещевой энцефалит; геморрагическая лихорадка с почечным синдромом THE CHARACTERISTIC OF DIFFUSION OF CASE RATE OF NATURAL AND FOCAL ILLNESSES IN TERRITORY OF PERM EDGE Influence of branches of a facilities on formation and maintenance of the centers of a vernal encephalitis and hemorrhagic fever with a renal syndrome is shown. The epidemiological situation on OF natural and focal diseases in thePerm edge for what reception of ranging of territory on an integrated parameter is offered is estimated. K e y w o r d s: endemic zoonosis; a vernal encephalitis; a hemorrhagic fever with a renal syndrome.